Learning Science is Easy and Fun Using Models Project-Based Learning - Haryanti, Yulia; Taruddin, Taruddin; Uslan, Uslan; Ginanjar, Gigin; Azizah, Wiwil (Sekolah Tinggi Agama Islam Solok Nan Indah, 2024)
Science learning is an important foundation in students' intellectual development and analytical abilities. However, students often feel bored and lose interest in science learning. This research aims to analyze the effects of using project-based learning in elementary schools. This research uses the method quantitative with a classroom action research approach. Data sources were taken using questionnaires and written tests from twenty-eight students in one elementary school in Indonesia. All data were analyzed using SPSS 18 software with descriptive analysis (percent). The results of statistical analysis show that the use of the project-based learning model has a positive effect on student attitudes and learning outcomes. This fact can be seen from changes in students' attitudes who are more active in learning, have greater curiosity than usual, and do not get bored quickly in learning. This fact is also supported by an increase in student learning outcomes from pre-cycle, cycle one, and cycle two. Therefore, implementing the project-based learning model is an alternative solution that teachers can use in science learning which has been considered difficult and boring.